Meminimalisir dampak negatif asap rokok menggunakan biofilter - Khabibah, Hanik (Maliki Interdisciplinary Journal, 2023)
Cigarette smoke is dangerous because free radical molecules have an unbalanced spin value and are highly reactive with other molecules. Free radicals are produced by incomplete combustion of cigarette smoke. Plant-based biofilters contain antioxidants and have the ability to scavenge free radicals from cigarette smoke, minimizing harmful levels in cigarette smoke, and thus promoting health.